The Teplá–Barrandian Unit: A Fascinating Archive Recording >600 My of Evolution of European Crust - Žák, Jiří; Kraft, Petr; Hajná, Jaroslava; Vacek, František; Svojtka, Martin; Kachlík, Václav; Ackermann, Lukas; Verner, Kryštof; Zulauf, Gernold; Dörr, Wolfgang; Tomek, Filip; Janoušek, Vojtěch; et al. (The Variscan Orogen of Central Europe, 2025)
The upper-crustal Teplá–Barrandian unit is a fascinating ‛archive’ that preserves a record of more than 600 My of extremely diverse geologic history of European lithosphere, from the initial accretion of juvenile arc-derived crust through several marine transgressions to Cenozoic intra-plate volcanism, uplift, and significant river incision. Thanks to the latter, we can enjoy reading this archive along tens of kilometers of superbly exposed continuous sections. This chapter focuses on the first, dynamic pre-Permian half of its history, whereas the post-Variscan intra-plate development is described elsewhere. The oldest rocks and hence recorded events are of Neoproterozoic (Ediacaran) to earliest Cambrian age, which, in fact, is a time span of origin of the whole Teplá–Barrandian unit at southerly high latitudes (ca. 50–60°S). Recent discoveries suggest that the Teplá–Barrandian unit preserves an extensive section across the former Cadomian active margin of Gondwana from outboard, strongly reworked relics of ca. 540 Ma oceanic crust through an accretionary wedge with olistostromes, tectonic mélanges, and dismembered portions of Ocean Plate Stratigraphy (OPS) to volcanic arc sequences and intra-arc basins, and perhaps also a strongly reworked, most inboard relict of a back-arc basin. Detrital zircon age spectra suggest that the Cadomian Teplá–Barrandian graywackes may have been sourced from a promontory of the Trans-Saharan belt or Saharan Metacraton. The accretion stopped at around 527 Ma and was followed by granitoid plutonism, perhaps resulting from slab break-off. This event marked a prolonged transition from an active to a passive margin during the Cambrian, recorded by continental and marine basins and accompanying volcanics. The geodynamic causes that terminated the Cadomian subduction still remain unclear and may range from a change in plate kinematics through ridge subduction to interaction with a mantle plume. The subsequent Tremadocian to Givetian passive margin stage is recorded in several kilometers thick deposits and basaltic volcanic complexes of the Prague Basin, a World famous, ʽclassicʼ field area of Lower Paleozoic stratigraphy and paleontology (together with adjacent units informally named ʽBarrandianʼ after a French paleontologist Joachim Barrande, 1799–1883). A continuous stratigraphic record over this time span can be divided into a lower siliciclastic and an upper carbonate package. The former indicates cold-marine shelf deposition and early Silurian global sea-level rise, whereas the latter documents warm-water deposition and the drift of the Teplá–Barrandian unit toward low, subtropical latitudes (ca. 10–20°S). The carbonate successions are conformably overlain by Givetian flysch, marking the onset of the Variscan orogeny. The Teplá–Barrandian unit was stuck in a broad collisional zone between Gondwana and Laurussia, but always remained an upper, overriding plate. The Variscan plate convergence resulted in the shortening/transpression in the Teplá–Barrandian upper crust and likely its elevation as an orogenic plateau during the Late Devonian to early Carboniferous times, coeval with the growth of a voluminous continental magmatic arc along its southeastern margin. The arc growth culminated with a magmatic flare-up at around 346 Ma, a magmatic event that recorded a major kinematic switch from convergence to gravity-driven collapse and normal shearing with a throw of at least 10 km, juxtaposing the upper crust against the high-grade Moldanubian orogenic root. The end of ductile normal shearing around the Teplá–Barrandian upper crust is bracketed by post-kinematic ultrapotassic plutons and dikes at around 337 Ma, representing the last major Variscan orogenic event in the central Bohemian Massif. The above described sequence of events and geodynamic processes has now been well established, especially due to immense scientific progress made over the past three decades. Yet, a number of issues still continue to be debated. The most controversial (and closely related) issues are (1) the amount of separation of the Teplá–Barrandian unit from Gondwana during the Early Paleozoic, i.e., whether it remained attached or was completely detached as a far-traveled terrane, with implications for the size and nature of oceanic domains in between, and (2) the pre-plutonic evolution of the Teplá–Barrandian/Moldanubian boundary, whether it was a complex, polyphase high-strain domain or a true oceanic subduction zone. Solving these two problems remains the most important challenge for future researc